Urethral Stricture Disease: Evaluation of the Male Urethra - Gelman, Joel (J Endourol, 2020)
The diagnosis of urethral stricture disease is often made when a man with obstructive voiding symptoms undergoes flexible cystoscopy (urethroscopy). However, a more complete and definitive diagnosis is then achieved when the urethra is subsequently evaluated with a retrograde urethrogram, and in many cases, a voiding cystourethrogram (VCUG). In situations where there is stricture disease involving the meatus or fossa navicularis that prevents the passage of adult flexible cystoscope, other testing appropriate in these cases include distal urethral calibration using bougie-a-boules and possibly the advancement of a pediatric cystoscope. It is only after the exact location and length and severity of the stricture is assessed that patients can be properly advised of all options before decision-making and the implementation of a treatment plan. This section will review the evaluation of the male urethra.